Read-out interfacing circuit for ISFET-based PH sensor VTH monitoring / Siti Nor Nadiah Nazari - Nazari, Siti Nor Nadiah (2012)
The Ion Sensitive Field Effect Transistor (ISFET) measure the pH-value and concentration of chemical activity by detecting ion hydrogen, H+ and this will change ISFET's threshold voltage, VTH. There is a need to extract the VTH changes using readout interfacing circuits (ROICs) instead of device characterization. This project focuses on the design of ROICs to detect the output voltage, VOUT, whenever there is any change in VTH. Four different ROICs are designed; a constant-voltage constant-current biasing circuit, a direct feedback complementary ISFET/MOSFET pair, an indirect feedback complementary ISFET/MOSFET pair and a zener-based bridge-type ROIC by modifications of standard MOSFET's model VTH value using LTSPICE is made to reflect different sensor response under different chemical concentration. In this paper, ROICs are analyzed by investigating the features of operation mode, changes in VOUT versus VTH, changes in VOUT versus temperature, and the power consumption of each circuit. Result shows that the CVCC circuit has a very sensitivity circuitry since the VOUT changes is 0.9mV per pH unit and has a stability of mode of biasing operation, the indirect feedback CIMP has the highest performance due to the temperature rises, and the direct feedback CIMP has lowest power consumption. As a conclusion, the changing in VTH will change the VOUT with the CVCC circuit giving the most sensitive response.